Maximum strength and power as determinants of on-ice sprint performance in elite U16 to adult ice hockey players - Kierot, M.; Stendahl, M.; Warneke, K.; Wirth, K.; Konrad, A.; Brauner, T.; Keiner, M. (Biology of Sport, 2024)
In ice hockey, speed strength is one of the major physical key performance indicators, which is significantly influenced by maximum strength. The objective of this study was to evaluate the age-dependent relationship of off-ice maximum strength and vertical jump performance with on-ice linear sprint performance, considering age and performance level. Ninety-one male youth and adult professional ice hockey players (age: 19.3 ± 5.49 years) were recruited and divided into four age groups: under 16, 18, 21 years old and professional elite players (Pro) (i.e., > 21 years). They were tested in maximal isometric strength, squat jump (loaded and unloaded), countermovement jump and on-ice sprint performance (15 m and 30 m linear sprint; 15 m flying linear sprint). Statistical analysis revealed that on-ice sprint performance correlated with isometric strength performance (r = |0.34|-|0.63|) and with off-ice jump performance (r = |0.61|-|0.77|) without an influence of age group or performance level. However, performance differed between age groups and performance level, the largest differences being found between the youngest age group (U16) and the Pro group (g = 0.966-3.281). The present study shows that maximum strength influences on-ice sprint performances in ice hockey players, as well as performance differences between age groups and professional players. Strength and jumping performance should therefore be included in regular performance testing in ice hockey. Since performance differences are observed for almost all strength and speed-strength performances of the youth teams to the Pros, training of these variables is strongly recommended to improve in the transition phase from junior to elite level.